UM ESTUDO DE [VAI SABER] NO PORTUGUÊS EM PERSPECTIVA CONSTRUCIONAL - SABRINA REGINATTO (2023)
This work focuses on micro construction [vai saber], considering its different uses and attributing special attention to its function as a Discourse Marker. Considering the general assumptions of the functionalist current of language studies, especially the Use-Based Models (Bybee, 2016) and Construction Grammar, it is assumed, in this work, that the basic form of language analysis is construction, considered a symbolic pairing of a structure with its meaning. The main objective of the research is to describe the interaction of three uses of [vai saber]: future periphrasis, doubtful marker and discursive marker, emphasizing features of the latter. For this, we base our analysis on the constructionalization concepts of Traugott and Trousdale (2021) and, regarding the study of Discourse Markers, we based on Traugott (2021) research and Risso, Silva and Urbano (2006). In order to characterize the construction and describe the possible uses in a synchronic way, we will explore ways that allow us to: a) map the defining properties of constructions: compositionality, schematicity and productivity (Traugott; Trousdale, 2021; Bybee, 2016); b) investigate and describe traits that constitute [vai saber] as a discourse marker from parameters, such as those proposed by Risso, Silva and Urbano (2006), in convergence with other approaches; and, c) verify the functionality of [vai saber] in different contexts of use. The study adopts a synchronic perspective based on the analysis of data collected from the Web/Dialects section of the CP-Portuguese Corpus (Fereira; Davies, 2006). The results show that: a) when periphrasing, [vai saber], as well as other similar expressions, can connect term, state-of-affairs or proposition. Supported by a still preserved verbal base, the construction [vai saber]PERFUT presents a subject and scopes a simple element, a real fact or event, or a possible fact; b) in its use as a dubious marker, [vai saber] already demonstrates “restrictions”: there is no subject and the illocutionary force cues suggest an interrogative contour, which combines with the scope of proposition, specifically, a possible fact and uncertain; c) as a DM, [vai saber] it always relates to possible propositions/facts, whose realization is uncertain. This tendency towards the non-factual is consistent with the total non-existence of the subject, syntactic disconnection and issues related to illocutionary force. The presence of these different uses in the language, based on formal and functional divergences between them, evidences synchronously a process of constructional change in [vai saber]. KEY-WORDS: future periphrasis, discourse markers, constructional changes.